2020
DOI: 10.5115/acb.20.014
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial influence of rhubarb on 5-fluorouracil-induced ileal mucositis and the combined role of aquaporin-4, tumour necrosis factor-α, nuclear factor-kappa B & matrix metalloproteinase-9 in rat model: histological study

Abstract: A 5-fluorouracil (5-FU) is used for cancer treatment despite its cytotoxic sequelae on healthy cells, especially the rapid proliferating ones. Intestinal mucositis is one of the most frequent chemotherapeutic debilitating sequelae. Rhubarb (Rh), an ancient herb, is known for its curing effect on gastrointestinal complications. This study aims to detect the role of aquaporin-4 (AQP-4), tumour necrosis factor-α (TNF-α), nuclear factor-kappa B (NF-κB), and matrix metalloproteinase-9 (MMP-9) in 5-FU-induced ileal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
2
2
1
Order By: Relevance
“…The mucosal damage in the present study was found to progress up to complete erosion of the mucosa. This was in agreement with other authors [ 28,29,30] .…”
Section: Discussionsupporting
confidence: 94%
“…The mucosal damage in the present study was found to progress up to complete erosion of the mucosa. This was in agreement with other authors [ 28,29,30] .…”
Section: Discussionsupporting
confidence: 94%
“…As previously reported, 5-FU at 150 mg/kg reduced body weight and food intake [38][39][40][41], but did not change water intake [38,42]. The body weight reduction could be explained, at least partially, by the associated reduction in food intake, but other factors could also be involved.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, mucositis was associated with diarrhea in other studies using 5-FU at the same dose and route of administration, but with different sexes and/or strains of rats. Thus, compared with mucositis, diarrhea does not seem to be a robust finding, with some rat strains showing vulnerability (female Dark Agouti [40,41]; male Sprague-Dawley rats [42]) and others displaying relative resistance to its development (male Wistar rats: present results and [8]).…”
Section: Discussioncontrasting
confidence: 55%
“…A higher dose of 5-FU was administrated to induce CIOM than the dose used to induce intestinal mucositis in murine (13). Since a single IP injection of 150 mg/kg of 5-FU successfully induced intestinal mucositis in a previous study (15), we IP injected 5-FU with a higher single dosage of 160 mg/kg, 200 mg/kg, or 240 mg/kg after anesthetizing rats using isoflurane. The maximum volume of IP injection in rats is known to be 20 ml/kg (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…There are technical considerations when developing CIOM in murine. A high-dose IP administration of 5-FU ranging from 100 to 500 mg/kg has been used for inducing CIOM in murine (15). Since the solubility of 5-FU at room temperature is about 12 mg/ml in water (14), more than 3 ml of 5-FU mixture administration is generally required for inducing CIOM in rats when considering rat's weight in the 7 th week (19).…”
Section: Histologic Evaluations (A) Large Granulation With Lymphocyte...mentioning
confidence: 99%